Transformers, Rescue Bots. [videorecording (DVD)] Jurassic adventure ([Publisher not identified], 2015)
The Rescue Bots, Chase, Heatwave, Blades and Bolder, along with a family of first responders, must tackle all sorts of problems to keep the town of Griffin Rock safe. This task just got prehistoric, as they must battle Doc Green's pet Dinobot Trex, along with other fantastic creatures.